Seniority rules, worker mobility and wages: Evidence from multi-country linked employer-employee data - Petri Böckerman; Per Skedinger; Roope Uusitalo (Research Institute of Industrial Economics (IFN), 2016)
We construct a multi-country employer-employee data to examine the consequences of employment protection. We identify the effects by comparing worker exit rates between units of the same firm that operate in two countries that have different seniority rules. The results show that last-in-first-out rules reduce dismissals of older, more senior workers, especially in shrinking multinational firms, and increase their bargaining power, resulting in a steeper seniority-wage profile.
Keywords: K31; J63; J32; J08; L51; 330; Multi-country linked employer-employee data; Employment protection legislation; Seniority rules